The joy of eating : a guide to food in modern pop culture - Glenn, Jane K. (ABC-CLIO, 2022)
"This volume explores our cultural celebration of food, blending lobster festivals, politicians' roadside eats, reality show "chef showdowns," and gravity-defying cakes into a deeper exploration of why people find so much joy in eating"--